Positive sire effects and adaptive genotype by environment interaction occur despite pattern of local maladaptation in roadside populations of an amphibian - Brady, Steven P.; Goedert, Debora (Copeia, 2017)
The global road network causes many negative ecological effects. Contrasting our knowledge of these effects, insights into evolutionary consequences of roads remain undeveloped. Here, we study a suite of populations of the Wood Frog that appear to be evolving maladaptively in response to road-adjacency. Specifically, when raised together in roadside pools, roadside populations survive at lower rates compared to populations away from roads. To begin to understand the cause of this survival disadvantage, we investigated potential parental and genetic sources of maladaptation. First, to assess whether parental effects might induce maladaptation, we measured adult body weight to length ratio ('relative weight') and its influence on offspring survival in a reciprocal transplant experiment across 12 populations. Next, to assess whether genetic effects might limit adaptive responses in offspring, we estimated genetic correlations between environments for survival and fitness-related traits. We found that relative weight was higher in roadside populations and, for males, had a positive influence on offspring survival. This demonstrates a novel transgenerational effect of Wood Frog adult males but suggests that this effect is not causing maladaptive survival. Genetic correlations indicated that a subset of roadside genotypes respond adaptively to road-adjacency despite population level maladaptive survival. This suggests that metapopulation dynamics and/or high levels of nonadditive genetic variance may be limiting adaptation or that insufficient time has elapsed for adaptation to occur. Together, these results highlight the complexity and scale of responses to a pervasive feature of landscape alteration revealed by evolutionary approaches.
Keywords: Amphibia; Rana sylvatica; adaptation; amphibian; dept.bio; environmental conditions; evolutionary biology; frog; genotype; genotype-environment interaction; heritability; local adaptation; metapopulation; population type; roadside environment; survival